Dukungan Sosial dan Self-Regulated Online Learning Belajar Matematika Siswa SMA di Masa Pandemi - Aina P. Khairani; Sumedi P. Nugraha (Jurnal Riset Psikologi, 2022)
Abstract. There are various obstacles occurring during the online learning process, one of which is in mathematics. To cope with these obstacles, self-regulated online learning (SROL) skills and good social support are deemed necessary. This study aimed to determine a relationship between social support and students' SROL in mathematics as seen from the social support sources in MIPA class students in SMA N “X” Kendal. The measuring instrument used in this study was the SROL scale from Arbiyah and Triatmoko (2016) with 24 items and the SSQC Gordon scale (2011) with 50 items. Total participants of this study are 220 MIPA class students in SMA N “X” Kendal from X to XII grade. Data analysis in this study used regression analysis. The results of data analysis showed the value of F = 8.416 with p value = < 0.001. These results indicated that social support could simultaneously predict the SROL of students in SMAN "X" Kendal in mathematics during the COVID-19 pandemic with an effective contribution of social support by 16.4% to SROL. Abstrak. Salah satu mata pelajaran yang paling menantang untuk dipelajari selama pembelajaran daring adalah matematika. Untuk mengatasi hambatan itu dibutuhkan kemampuan self-regulated online learning (SROL) dan dukungan sosial yang baik. Penelitian ini bertujuan untuk mengetahui seberapa besar hubungan dukungan sosial dengan SROL siswa pada mata pelajaran matematika dilihat dari sumber-sumber dukungan sosialnya di kelas MIPA SMA N “X” Kendal. Penelitian ini menggunakan alat ukur berupa skala SROL dari Arbiyah dan Triatmoko (2016) yang berjumlah 24 aitem dan skala SSQC Gordon (2011) yang berjumlah 50 aitem. Partisipan penelitian ini berjumlah 220 siswa kelas X sampai XII MIPA SMA N “X” Kendal. Hasil analisis regresi data diperoleh nilai F= 8,416 dengan nilai p= < 0,001. Hasil tersebut menunjukkan bahwa dukungan sosial secara bersama-sama dapat memprediksi SROL siswa SMA N “X” Kendal pada mata pelajaran matematika di masa pandemi COVID-19 dengan sumbangan efektif dukungan sosial sebesar 16,4% terhadap SROL.